Is development aid superfluous? Aid has not lived up to expectations - Ulrich Hiemenz (Intereconomics, 1986)
The benefits of development aid have been increasingly called into question in recent times. In such aid superfluous or indeed harmful? Ulrich Hiemenz and Franz Nuscheler address this issue in the following two contributions.
Keywords: 330; Development Aid